The United States in Kazakhstani public opinion: Double-edged cultural influence and the collateral damage of foreign policy. Issue 2 (July 2021) - Laruelle, Marlene; Royce, Dylan
This article employs surveys by Gallup, the Central Asia Barometer, and the Barometer of Eurasian Integration, as well as focus groups that were commissioned as part of this research, to argue (1) that Kazakhstani perceptions of the United States compare unfavorably to perceptions of China and especially of Russia; (2) that Russian influence is a minor or nonexistent cause of the United States' poor image; (3) that US cultural influence has an ambiguous effect on the country's image in Kazakhstan, due to a "clash of values" between conservative Kazakhstani society and relatively liberal US cultural exports; (4) that the United States' foreign policy, especially its violation of other states' sovereignty, has an unambiguously negative effect on its image among Kazakhstanis; and (5) that the resulting relatively negative image of the United States translates into reluctance to build or maintain ties with it. In conclusion, we highlight areas in which the United States–Kazakhstan cooperation is likely to receive a better reception.